Prisoners of the home front: A social study of the German internment camps of southern Quebec, 1940-1946. - Auger, Martin F. (University of Ottawa (Canada), 2000)
During the Second World War (1939--1945), five internment camps were created on the south shore of the St. Lawrence river for the incarceration of male individuals of German descent. They were known as Farnham, Grande Ligne, Ile-aux-Noix, Sherbrooke (Newington) and Sorel. Their goal was to neutralize any potential threat to the defence of the Canadian nation. With the entire country being mobilized for war, the security of the homefront was necessary. Any person suspected of sympathizing with the enemy was perceived as a potential "spy and Saboteur" and was incarcerated in internment camps. Individuals of German origin were no exception. During the first phase of southern Quebec's internment operation, 1940--1943, civilians formed the bulk of the inmates while during the second phase, 1942--1946, it was prisoners of war. This thesis analyzes how the region's internment operation developed. It deals primarily with the issue of life behind the barbed wires and how psychological strains came to affect inmates. It also looks at how Canadian authorities attempted to counter such problems by introducing labour projects and re-educational programs. This case study of southern Quebec demonstrates that the internment camp operation in Canada was an integral part of the effort to produce total war.
Keywords: History, Canadian.